Effect of Medicated Enema and Herbal Formulation over Inflammatory Biochemical Markers in Rheumatoid Arthritis: A Case Report - Vaishnavavi Subhash Bodhe; Punam Gauravav Sawarkar; Gaurav R Sawarkar (Journal of Clinical and Diagnostic Research)
Rheumatoid Arthritis (RA) is the predominant type of autoimmune inflammatory arthritis, affecting approximately 0.75% of the Indian population. It is a painful condition that impacts an individual’s overall physical and mental well-being, making daily tasks challenging. This is a single case study primarily aimed at investigating the efficacy of a medicated enema (Vaitaran Vasti) and oral herbal formulations on the inflammatory biochemical parameters of RA. The present case involves a 53-year-old female patient who was diagnosed with RA a few months ago based on clinical symptoms, such as multiple joint pain and morning stiffness throughout the body lasting for about 60 to 90 minutes. The patient was assessed based on clinical features and biochemical parameters, which are gold standard measures in conventional medicine for RA. After undergoing treatment, the patient’s quality of life improved significantly due to a substantial reduction in all clinical symptoms, including pain, stiffness, swelling, and bipedal oedema. Moreover, the values of the RA test and CRP levels were significantly reduced from 64 IU/L and 96 mg/L to 16 IU/L and 24 mg/L, respectively, after 15 days. The patient did not require oral pain relievers. Ayurvedic treatment yielded excellent outcomes in this case, especially when conventional medical options were limited. Exploring Ayurveda as a treatment avenue has provided a glimmer of hope.